2007
DOI: 10.1042/bj20061427
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI)-stimulated STAT3 tyrosine phosphorylation and nuclear translocation in human airway epithelial cells requires Lck

Abstract: Chronic inhalation of low amounts of Cr(VI) promotes pulmonary diseases and cancers through poorly defined mechanisms. SFKs (Src family kinases) in pulmonary airway cells may mediate Cr(VI) signalling for lung injury, although the downstream effectors of Cr(VI)-stimulated SFKs and how they relate to pathogenic gene induction are unknown. Therefore SFK-dependent activation of transcription factors by non-cytotoxic exposure of human bronchial epithelial cells to Cr(VI) was determined. Protein–DNA binding arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
7
27
0
Order By: Relevance
“…These studies used the BEAS-2B cells to model the terminal bronchiolar epithelial responses to Ni. While these cells are SV40 immortalized, we have demonstrated that their responses to metals are nearly identical to primary normal human bronchiolar epithelial cells cultured on an air/liquid interface (27) and mouse bronchiolar epithelium in vivo (29). Induction of MT after Ni exposure in these cells closely matches responses observed in mouse lungs (33), and thus the mechanisms for this induction in BEAS-2B cells are likely to be broadly applicable.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…These studies used the BEAS-2B cells to model the terminal bronchiolar epithelial responses to Ni. While these cells are SV40 immortalized, we have demonstrated that their responses to metals are nearly identical to primary normal human bronchiolar epithelial cells cultured on an air/liquid interface (27) and mouse bronchiolar epithelium in vivo (29). Induction of MT after Ni exposure in these cells closely matches responses observed in mouse lungs (33), and thus the mechanisms for this induction in BEAS-2B cells are likely to be broadly applicable.…”
Section: Discussionmentioning
confidence: 51%
“…The medium was changed 12 to 16 hours before the experiment. Under these conditions, the BEAS-2B responses to metals are similar to responses in primary human bronchial epithelial cells grown in air/ liquid interface cultures (27). Dko7 cells are SV-40 immortalized mouse embryonic fibroblasts (MEF) derived from MTF-1 double knockout embryonic stem cells (28).…”
Section: Cell Culturementioning
confidence: 99%
“…Previous studies showed that Cr(VI) stimulates IL-6 mRNA levels and STAT3 phosphorylation in human airway epithelial cells [34]. STAT3 binding to the miR-21 promoter upon IL-6 induction has been reported previously [30].…”
Section: Resultsmentioning
confidence: 69%
“…Moreover, STAT3 is upregulated in both premalignant tumors (papillomas) and squamous cell carcinomas of mouse skin induced by topical treatment with DMBA + TPA (Chan et al , 2004). Cr(VI)-induced transactivation of STAT3 has been reported in human airway epithelial cells (O’hara et al , 2007). Cr(VI) exposure in BEAS-2B cells increased Stat3 activation and phosphorylation whereas treatment of luteolin suppressed them.…”
Section: Discussionmentioning
confidence: 98%
“…STAT3 is linked to inflammation-associated oncogenic transformation, by promoting pro-oncogenic inflammatory pathways, including nuclear factor-κB (NF-κB) and interleukin-6 (IL-6) (Yu et al , 2009). Previous studies demonstrated a prolonged STAT3 activation and transactivation of IL-6, with Cr(VI) exposure in human epithelial cells (O’hara et al , 2007). Inducible nitric oxide synthase (iNOS), one of the three isoforms of nitric oxide synthase, catalyzes the oxidative deamination of l-arginine to produce citrulline and nitric oxide (Chen et al , 2005).…”
Section: Introductionmentioning
confidence: 88%